Identificação e caracterização de plantas poliploides de Heliconia chartacea var. Sexy Pink - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
One of the sectors that have the highest growth rate in the national and international market is floriculture. Ornamental plants are distinguished by their beauty, which enchant both through their exotic forms and by the variation of colors, among which stands out the Heliconia chartacea var. Sexy Pink. The search for consumers for news has forced producers to launch, more and more quickly, new varieties to maintain competition in this productive segment. In this sense, biotechnological research was carried out by Embrapa Amazônia Occidental to induce polyploidy in vitro by somatic doubling using colchicine in three concentrations (0.01%, 0.05% and 0.1%) in order to obtain a Higher rate of genetic variability causing larger and better plants, and as a bridge for gene transfer between different levels of ploidy. In this context, the objective of this work was to evaluate the plants established in the field, from in vitro polyploidy induction assays to determine the morphological, physiological, molecular and productive characteristics of 42 clones of H. chartacea var. Sexy Pink. The characterization analyzes were performed by means of 49 morphological and agronomic descriptors, determination of the number of polymorphic loci by AFLP, characterization of leaf blade structure and stomatal density evaluation by means of microscopy, besides identification of the ploidy level by citometry of flow. As the genotypes 13, 20, 36, 37 and 40 did not present inflorescences during the two years of evaluation and did not present any other characteristic of commercial interest, they were considered unfit for selection for future selection and breeding work. The genotype 35 showed the highest morphological variations with changes in the position and color of the inflorescence, besides having the edges of the whole leaf blade. Clone 18 showed plant height and inflorescence size reduced. Clone 26 presented total defoliation during flowering, which makes this genotype more interesting for landscaping. Combinations of the primers used for AFLP analysis revealed a total of 519 bands, ranging from 100 to 800 base pairs. The total number of loci per primer varied from 157 to 188, while the amount of genetic variation obtained by analysis of molecular variance showed that 99.67% of the genetic variability is within the treatments with colchicine analyzed, and only 0.33 % Among treatments of H. chartacea clones. The stomata of all clones showed tetracytic morphology and guard cells without significant alterations. The highest ED were observed in clones 1 and 14 for the adaxial part of the leaves, whereas for the abaxial part, clones 10, 12 and 14 were the ones with the highest values. The lowest values were verified in clones 7 and 35 for the adaxial part and 7 and 13 for the abaxial part of the leaves. The work allowed the identification of 4 tetraploid and 11 mixoploid genotypes by the flow cytometry technique. Helping in the identification of potential genotypes for genetic improvement program and future in obtaining new varieties.
Keywords: Flores tropicais; Melhoramento genético; Helicônias; Citometria de fluxo; CIÊNCIAS AGRÁRIAS: AGRONOMIA